The Transfer Features Phraseological Units of Modern German (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the problem of translation of German phraseological units, methods of translation of German phraseological units into Ukrainian.
Keywords: phraseological units; borrowings; transformation; phraseology